Ukrainian-language Adaptation of the Basic Psychological Need Satisfaction Scale - Valerii Olefir; Valerii Bosniuk (Insight: the psychological dimensions of society, 2024)
The study’s main aim was to adapt and validate the psychometric properties of the Ukrainian version of the Basic Psychological Need Satisfaction Scale, which is based on E. Deci and R. Ryan’s meta-theory of self-determination. During the work, special emphasis was placed on proving the questionnaire’s structural validity. Based on theoretical considerations and a review of contemporary approaches to studying multidimensional constructs, we assumed that the basic psychological needs assessment scale has a complex bifactor structure. Methods. Two bilingual psychologists used the reverse translation method to translate the scale from English to Ukrainian. 548 people (62.0% women, 38.0% men) took part in the study using the Google Forms online service. The obtained data was analyzed using the statistical software environment Mplus and JASP. The results of our study revealed that the theoretical a priori three-factor model, in which each psychological need is a distinct independent factor, does not match empirical data. A bifactor exploratory model of a shortened version of the questionnaire with up to sixteen items showed a good fit and the best representation of the subjects’ evaluations of their needs being met. The psychometric reliability analysis revealed that the questions were highly consistent for both the general factor (need satisfaction) and its specific subscales (autonomy, competence, and relatedness). The obtained statistically significant theoretically expected correlations between questionnaire scales and variables indicating subjective well-being attest to the diagnostic instrument’s nomological validity in relation to external constructs. The scale’s measurement invariance by gender has been proven separately; it works equally well in groups of females and males. Conclusions. The adapted version of the Basic Psychological Need Satisfaction Scale for the Ukrainian-speaking environment meets widely accepted psychometric standards and is recommended for use in psychodiagnostic practice with a high level of accountability for decisions made.